Efficiency Determinants in Brazilian Football Clubs - Marcelo Machado de Freitas (FUCAPE Business School, 2017)
The aim of this study is to analyze the efficiency of Brazilian football clubs in generating revenues and the reasons behind it. To achieve this goal, we applied quantitative methods including Data Envelopment Analysis and Tobit regression modeling to data on the best clubs from 2012 to 2014, according to the Brazilian Football Confederation ranking. The results allowed for the inference that the largest Brazilian clubs, such as Grêmio (RS), Palmeiras (SP) and Vasco (RJ), were not efficient in any period under analysis. Others, such as Guarani (SP) and Guaratinguetá (SP), were efficient in all of years under consideration. With the Tobit regression model, we were able to determine that winning titles and the elite status of a given club are decisive factors in achieving efficiency. Included among the strategies that allow for greater efficiency in Brazilian clubs are the better utilization of stadiums and club assets, maximization of the financial worth of player popularity, and joining these with titles and a place in the A Series. Finally, the results of this study contribute to the strategic development of the football business, highlighting the positive effects that efficiency yields for clubs, thus supporting the growing body of research on sports management in Brazilian academia.